Developing a vision strategic planning for the school librarian in the 21st century - Crowley, John D. (John Dennis) 1947- (Libraries Unlimited professional guides in school librarianship., 2011)
This text shows teacher librarians how to become leaders in their schools and apply their unique skills and insight to develop a timely and meaningful vision for the school's library.